PENGARUH EARNING PER SHARE, RETURN ON EQUITY, PRICE EARNING RATIO, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM (PERUSAHAAN YANG TERGABUNG DALAM INDEKS LQ45 DI BURSA EFEK INDONESIA) - Ayu Kemalasari; Desrini Ningsih (JURNAL AKUNTANSI BARELANG, 2019)
This study aims to analyze the effect of Earning Per Share, Return On Equity, Price Earning Ratio, and Debt to Equity Ratio on stock price of the companies listed in the LQ45 index for the period 2013-2017. The results showed that EPS had a significant effect on stock prices with a sig value of 0,000. ROE had no significant effect on stock prices with a sig value of 0,131. PER had a significant effect on stock prices with a sig value of 0,000. DER had no significant effect on stock prices with a sig value of 0,572. EPS, ROE, PER, and DER variables simultaneously have a significant effect on stock prices with a sig value of 0,000. The determination coefficient is 0,839, which means the EPS, ROE, PER, and DER variables is 83,9% affect the stock price while the remaining 16,1% is influenced by other variables not examined in this study.